Analysis of ship food inventory control using the economic order quantity (EOQ) method - Nabila, Aldhea; Maliki , Farmansjah (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
This study analyzes the control of food inventory aboard vessels operated by Bernhard Schulte Shipmanagement (BSM) using the Economic Order Quantity (EOQ) model. Employing a quantitative approach, the research examines 12 months of food procurement and consumption data from the PIS SMT vessel. Data were collected through documentation review and direct observation and analyzed using QM Software to calculate key EOQ parameters, including optimal order quantity, ordering frequency, reorder point, safety stock, and maximum inventory level. The results indicate that implementing the EOQ method significantly optimizes onboard food inventory management. The optimal ordering frequency was reduced from 12 to 3 times per year for perishable items and to 2 times per year for non-perishable items. Furthermore, the total annual inventory cost under the EOQ model is USD 1,517.83—a 62.71% reduction compared to the current policy cost of USD 4,927.85. These findings demonstrate that the EOQ method offers a substantially more cost-effective and efficient system for managing shipboard food provisions.